Surgical laparoscopy in uterine cervix cancer at EsSalud Huancayo Hospital - Molina Loza, Ernesto (2015)
Introduction: Cervical cancer is the most common cause of death in Peruvian central highlands. Surgical treatment (hysterectomy and total laparoscopic radical hysterectomy plus pelvic lymphadenectomy) is the best therapeutic resource in the early cancer stage (IA1, IA2 and IB1). One year ago we started laparoscopic surgical treatment in these stages at Hospital IV Huancayo Gynecology Department. Objectives: To review outcomes of laparoscopic hysterectomy for microinvasive cervical cancer. Design: Retrospective study. Setting: Gynecology Service, Hospital IV Huancayo, EsSalud, Junin, Peru. Patients: Twelve women subjected to laparoscopic hysterectomy for cervical microinvasive carcinoma. Interventions: Six women with preoperative diagnosis by cervical conization and clinical stage IA1 underwent laparoscopic hysterectomy with 59.16 minutes operative time and 4.1 days hospital stay. Other six women with clinical stage Ia2-Ib1 underwent laparoscopic radical hysterectomy plus pelvic lymphadenectomy with operative time 3 hours and 58 minutes, and hospital stay of 10.1 days. Main outcome measures: Clinical cancer cure. Results: All diagnoses were confirmed by the surgical specimen and all were theoretically cured (negative margins, negative  lymph nodes); one patient had complications that required prolonged stay (8.3%). Conclusions: Total laparoscopic hysterectomy and laparoscopic radical hysterectomy plus pelvic lymphadenectomy can be performed faster and more radically compared with conventional laparotomy. Both are feasible and safe interventions that ensure cure in microinvasive cervical carcinoma.